Relating shape to human aesthetic evaluations of harvest blocks from an aerial perspective. Issue 8 (17th November 2018) - Liu, Jingshu; Chamberlain, Brent C.; Kozak, Robert A.; Meitner, Michael J.; Nesbitt, Lorien
ABSTRACT: Forest planners employ various techniques to mitigate the visible effects of harvesting, including by manipulating the shape of harvest blocks. Shape is a common indicator of preference in aesthetic evaluations of landscape and harvest block design. However, the majority of perception-based research in the field of landscape aesthetics has focused on the perspective view. This study investigates the perceptual effects of two shape characteristics: complexity and image mode, as viewed from the air. Order and subjects' area of study were also tested. Forty-five aerial images of harvest blocks and 45 digitally-manipulated harvest block shapes were used as the harvest and shape image sets, respectively. Seventy-five subjects rated each image for preference. Complexity was the strongest predictor of preference. Preference increased as complexity level increased, regardless of the image mode in which the shapes were presented. Subjects with an environmental focus in their area of study demonstrated a more prominent complexity effect than those from non-environmental fields. Both image mode and area of study had small but significant effects on preference ratings. These results confirm previous findings pertaining to complexity in psychology and landscape aesthetics, in which complexity, as a characteristic of shape, plays a role in predicting preference.